2017
DOI: 10.1186/s40249-017-0300-8
|View full text |Cite
|
Sign up to set email alerts
|

Putting the treatment of paediatric schistosomiasis into context

Abstract: Despite increased international efforts to control schistosomiasis using preventive chemotherapy, several challenges still exist in reaching the target populations. Until recently, preschool-aged children had been excluded from the recommended target population for mass drug administration, i.e. primary school children aged 6–15 years. Our studies and those of others provided the evidence base for the need to treat preschool-aged children that led to recommendations by the World Health Organization to include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…In the Expanded Programme on Immunisation (EPI) in sub-Saharan Africa these children are accessed successfully through primary health care (PHC) programmes. In this current study in Zimbabwe, these young children were also accessed through the PHC [ 29 ]. Given that monitoring of reinfections is dependent on the religious participation to follow up programmes, there is a need to ascertain to what extent do PSAC comply to successive participation and if the PHC system is effective regards the accessibility of PSAC for participation in schistosomiasis control programmes.…”
Section: Introductionmentioning
confidence: 99%
“…In the Expanded Programme on Immunisation (EPI) in sub-Saharan Africa these children are accessed successfully through primary health care (PHC) programmes. In this current study in Zimbabwe, these young children were also accessed through the PHC [ 29 ]. Given that monitoring of reinfections is dependent on the religious participation to follow up programmes, there is a need to ascertain to what extent do PSAC comply to successive participation and if the PHC system is effective regards the accessibility of PSAC for participation in schistosomiasis control programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported an association between the enlargement of the left liver lobe and S. mansoni infection and its intensity [11,31,32]. The main concern here, is the development of S. mansoni related hepatosplenic morbidities at such young age and the fact that, to date this age group is not considered for MDA with praziquantel [35,39,41]. At the time when these children will be attending primary school, they are at risk of having already developed advanced stages of hepatosplenic disease.…”
Section: Discussionmentioning
confidence: 98%
“…In our present study, almost 41% of the pre-school children were missed by KK technique. Taking into account that the peadiatric formulation of praziquantel will be available in the near future [35,39], which will allow including of PSAC into the MDA program, it is important to include a more sensitive diagnostic test for case detection in this age group and for monitoring of drug efficacy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Global control programs currently exclude preschool age children due in part to lack of evidence for efficacy and safety in this group, but clinical trials are in progress to develop safe delivery methods for praziquantel for children under 6 years old. 26,27 Complementary strategies that focus on environmental interventions should be promoted in tandem with MDA to help reduce transmission among this vulnerable age group. 28 for use under a CC0 license.…”
Section: Discussionmentioning
confidence: 99%